Teratogenic Effects Across Species: Insights from Animal Studies to Human Health Implications - Sharma, Ravi Dutt; Kumar, Daniel Deepak (Journal of Neonatal Surgery, 2025)
Teratogenicity refers to the ability of substances to cause developmental malformations in embryos or fetuses, posing significant challenges in pharmacology and toxicology, especially in the context of drug safety during pregnancy. Animal models have long been instrumental in studying the mechanisms of teratogenesis, providing insights into the molecular, genetic, and environmental factors that contribute to developmental defects. However, despite their utility, animal models have limitations due to species-specific differences in drug metabolism and development. Emerging technologies, including CRISPR gene-editing, nanotechnology, and organ-on-chip systems, offer promising alternatives that could enhance the accuracy of teratogenicity testing while reducing the ethical concerns associated with animal use. This paper explores the role of animal models in teratogenicity research, discusses the challenges of translating animal findings to human health implications, and highlights the potential of cutting- edge technologies to revolutionize the field, leading to better predictive accuracy and safer drug development